"Direct" sowing of grain crops after potatoes. Issue 1 (1st December 2022) - Volkov, A I; Prohorova, L N; Bogdanov, K V
Abstract: The effectiveness of the use of "direct" sowing in the cultivation of grain crops in the north-east of the Non-Chernozem zone of the Russian Federation has been revealed. Field experiments were carried out in 2019-2021 on medium loamy low-humus gray forest soils with a high content of mobile phosphorus and exchangeable potassium. The weather conditions during the years of the experiments differed both in terms of heat supply and the amount of precipitation. The objects of the study were: winter wheat of the Moskovskaya 39 variety, spring wheat – Arhat, malting barley – Elf, fodder barley – Pamyaty Rodinoy, corn for silage and grain hybrid NK Gitago. "Direct" sowing was carried out using the Primera DMC (Amazone) sowing complex with the simultaneous application of mineral fertilizers for the maximum planned yield of each crop. On average, the maximum (3.43 t/ha) grain yield when using "direct" sowing was formed when cultivating corn, and the minimum (1.86 t/ha) – malting barley. In the production of these crops, the highest (2.42) and the lowest (1.85) energy efficiency coefficient, respectively, was also revealed. An analysis of economic indicators testified to the expediency of using "direct" sowing in the cultivation of winter wheat, which was reflected in obtaining the maximum (73.3%) level of profitability. The minimum (31.5%) level of profitability was noted in the cultivation of malting barley, which is explained by the high degree of material and labor costs and its relatively low yield. The profitability of the production of other types of crop products was 1.18-1.94 times lower. In general, the agronomic, energy and economic assessment showed bright prospects for the cultivation of winter wheat and maize for grain using the "direct" seeding method after potatoes.